Lowering systolic blood pressure to 120 mmHg or The Lancet's true grit. (1st June 2021) - Messerli, Franz H; Brguljan, Jana; Rexhaj, Emrush; Sever, Peter; Pocock, Stuart; Taddei, Stefano
Graphical Abstract: